Inventory Management Strategies to Enhance Resilience Among Automotive Suppliers - Ramdass, K.R.; Nair, T. (South African Journal of Industrial Engineering, 2025)
The increasing vulnerability of supply chain disruptions in the automotive industry had an adverse impact on production schedules, financial performance, and customer satisfaction. This research comprehensively analyses current practices, case studies, and interviews with industry experts to propose a framework for implementing resilient inventory management strategies. Examining the root causes and effects of supply chain disruptions has identified areas where strategic interventions could mitigate risks and highlight the role of digital technologies, such as the Internet of Things, in optimising inventory management strategies. The findings emphasise the importance of real-time data analytics, diversifying suppliers, and improving the resilience of automotive suppliers.